Potential of MISFET with HfN gate dielectric formed by ECR plasma sputtering. Issue 7 (1st March 2013) - Han, H.S.; Han, D.H.; Ohmi, S.
Abstract : A report is presented on a Al/HfN/p‐Si(100) n‐MISFET with excellent electrical properties that inserts a 4 nm‐thick HfN gate dielectric with equivalent oxide thickness of 0.7 nm formed by electron‐cyclotron‐resonance plasma sputtering. The threshold voltage (Vth ) of the device was 0.05 V. The on/off ratio and subthreshold swing at W/L = 90 µm/5 µm were ∼10 3 and 200 mV/dec., respectively. In particular, the n‐MISFET exhibits IDS, sat = 20.2 µA/μm and gm = 20.5 mS/mm. This is the first report of n‐MISFET characteristics with HfN gate dielectric.